2017
DOI: 10.21743/pjaec/2017.06.08
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the Occurrence of Methicilin Resistant Staphylococcus aureus (MRSA) Infections in Hyderabad, Pakistan

Abstract: Staphylococcus aureus is a potential pathogen of hospital and community related infections. It secretes toxins or the enzymes as virulence factor of mild to severe infections and show resistance to beta-lactam antibiotic including penicillin, methicillin, oxacillin and now vancomycin that could alarm of equal risk factors of Methicillin Resistant Staphylococcus aureus (MRSA) infections in the patients. The survey report of 381 patients of Hyderabad, Pakistan was collected from March 2013 to June 2014 in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
2
2
Order By: Relevance
“…Self-medication along with inappropriate dispensing of antibiotics among patients are some of the other weaknesses in the clinical health system in Pakistan that further enhance the prevalence of antibiotic resistance [31,32]. In contrast to the previous reported results of different studies [12,33,34], no vancomycin resistant S. aureus were identified in the present study. Vancomycin intermediate resistant and vancomycin resistant S. aureus (VISA and VRSA, respectively) are a serious public health concern.…”
Section: Discussioncontrasting
confidence: 78%
“…Self-medication along with inappropriate dispensing of antibiotics among patients are some of the other weaknesses in the clinical health system in Pakistan that further enhance the prevalence of antibiotic resistance [31,32]. In contrast to the previous reported results of different studies [12,33,34], no vancomycin resistant S. aureus were identified in the present study. Vancomycin intermediate resistant and vancomycin resistant S. aureus (VISA and VRSA, respectively) are a serious public health concern.…”
Section: Discussioncontrasting
confidence: 78%
“…The ciprofloxacin resistance (33.7% and 47%) was lower in these studies as compared to our study (75%). 9,11,12 In present study, MRSA resistance to gentamicin was found to be 62.5%, while the studies conducted in Lahore and Peshawar reported higher resistance 97.6% and 100% respectively. 9,10 MRSA resistance to Rifampicin was found 25.0 %, while low resistance of rifampicin such as 18.8%, 14.0% and 7.0 % reported in previous studies.…”
Section: Discussioncontrasting
confidence: 40%
“…A study conducted in Hyderabad, Pakistan reported 75% samples positive for MRSA. 19 We should improve detection methods for pathogens to avoid misuse of antibiotics and to decrease antibiotic resistance. These methods should be as much improved so that we detect pathogens in early infection.…”
Section: Discussionmentioning
confidence: 99%